Alterations in distribution of tenascin, fibronectin and fibrinogen in vulval lichen sclerosus. - Farrell, A; Dean, D; Charnock, F; Wojnarowska, F (2000)
BACKGROUND: The pathophysiology of lichen sclerosus remains uncertain. The clinical features, including increased fragility and scarring, and the histology suggest that significant reorganisation of the extracellular matrix is occurring. Tenascin, fibrinogen and fibronectin are extracellular matrix components that play a significant role in tissue remodelling, for example during wound repair. AIM: To examine the distribution of tenascin, fibrinogen and fibronectin in vulval lichen sclerosus. MATERIALS AND METHODS: Immunohistochemical staining was performed to study the distribution of tenascin, fibronectin and fibrinogen in 16 specimens of untreated vulval lichen sclerosus and 1 specimen of extragenital lichen sclerosus. Haematoxylin and eosin staining of the specimens was also performed to identify the position of the pale staining homogenous zone/zone of sclerosis and the inflammatory infiltrate below this. The control tissues studied included biopsies taken from the uninvolved thigh of 13 of the lichen sclerosus patients and 6 samples of normal vulva tissue obtained during gynaecological procedures from women of similar age to the lichen sclerosus women. RESULTS: All the lichen sclerosus specimens demonstrated increased immunostaining of tenascin in the upper dermis and comparing this with the haematoxylin and eosin staining this corresponded to the zone of sclerosis with relatively little tenascin staining associated with the inflammatory band. In 14 out of the 16 vulval lichen sclerosus specimens and the extragenital lichen sclerosus specimen fibrinogen immunostaining was increased in the upper dermis which corresponded--in haematoxylin and eosin staining --to the zone of sclerosis. There was also slightly increased fibrinogen staining in the mid dermis which corresponded to the inflammatory band. Fibronectin staining was reduced in the upper dermis of 12 of the vulval lichen sclerosus specimens and the extragenital lichen sclerosus specimen which corresponded to the zone of sclerosis. However, in 14 of the vulval lichen sclerosus specimens and the extragenital lichen sclerosus specimen, fibronectin was slightly increased in the mid and deeper dermis which corresponded to the zone of inflammatory cells and the area below this. There was also increased fibronectin staining around blood vessel walls both in the mid dermis and within the zone of sclerosis. CONCLUSION: The distribution of tenascin, fibrinogen and fibronectin is altered in lichen sclerosus and the alteration in these extracellular matrix components may be relevant to the initiation of scarring in lichen sclerosus and the associated increased skin fragility.